POTENSI BEBERAPA JENIS TEPUNG RUMPUT LAUT UNTUK MENINGKATKAN KADAR HDL (HIGH DENSITY LIPOPROTEIN) PLASMA TIKUS WISTAR HIPERKOLESTEROLEMIA (Jurnal Teknologi Pangan, 2013)
Several types  of  seaweed in  Bali  has  been generally  consumed  by  local  people  as vegetable, such as Caulerpa spp. (local name Bulung Boni), Gracillaria spp (local name Bulung Sangu) and Euchema spinosum, but has not been reported  its potential effect to increase high density  Lipoprotein  (HDL)   levels.  Therefore it  is  necessary    to  determine  of  plasma HDL cholesterol  level  of  Wistar  rat  after  treated  Caulerpa  spp,  Gracillaria  spp. and  Euchema spinosum. This experimental study used completely  randomized design. Research using  a total of  32  Wistar rats  divided  into  eight  sample  groups  of  equal  size,  all  fed  with  a  diet  high  in cholesterol content. The eight sample groups were respectively designated as negative control group,  positive  control  group,  and  six    treated  sample  groups,  respectively  fed  orally  with  a dose of 1 g and 1,5 g seaweed flour  of Caulepa spp.  1g and 1,5 g of Gracilaria spp., and 1 g and  1,5  g  Euchema  spinosum  per  100g  body  weight  per  day.  Each  treatment  was  repeated four times.  Our  study showed  that  rat fed with  high  cholesterol  diet and  treated Caulerpa  spp., Gracilaria spp., and E.spinosum with a dose of 1 g and 1.5 g/100 g body weight rat / day were associated  with  statistically  significantly  increased plasma HDL level (p  <0.05) as compared with those  of rats fed with high-cholesterol diet without treated  Caulerpa spp., Gracilaria spp., and E.spinosum. The  studied  concuded  that  plasma  HDL  level  of  Wistar  hypercholesterolemia  fed Caulerpa  spp.,  Gracilaria  spp.,  and  E.spinosum  flour with  dose  of  1  g  or  1,5  g higher  than Wistar rat without treated seaweeds flour. Rats fed E.spinosum with dose of 1.5 g , the plasma HDL level highest than the other treatment.Keywords : Caulerpa spp., Gracilaria spp.,  E.spinosum, HDL,  hypercholesterolemic